Strategic Management of Hybrid Counseling: A Novel Approach to Addressing Quarter-Life Crisis Among University Students in Indonesia - Walid, Muhammad; Najah, Aninda Tri Safinatun; Ula, Naila Kholisotul; Turrohmah, Nadya Salsabilla (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to analyze the Hibryd Counseling Service (Islamic counselling) strategy to effectively prevent Quarter Life Crisis and prepare students who become agents of change for a better direction in college. Using interview, observation, and documentation methods, this study seeks to obtain data on the phenomenon of quarter-life crisis and the new approach. The data sources include critical stakeholders in the guidance and counselling laboratory. Data analysis was carried out through data transcription, coding, and categorization. The study results indicate that Islamic counselling is valuable in guiding individuals to overcome quarter-life crises by aligning psychological and spiritual aspects. Islamic counselling significantly contributes to helping individuals overcome quarter-life crises with a holistic approach involving spiritual, psychological, and social factors. Integrating Islamic values in counselling forms a solid framework to support young individuals facing life challenges. These findings provide important insights related to the effectiveness of the Islamic counselling approach in overcoming quarter-life crises through the integration of spiritual, psychological, and social values.